Genome-Wide Identification of Wheat ZIP Gene Family and Functional Characterization of the TaZIP13-B in Plants - Li, Song; Liu, Zihui; Guo, Linlin; Li, Hongjie; Nie, Xiaojun; Chai, Shoucheng; Zheng, Weijun (Frontiers in Plant Science, 2021)
The ZIP (Zn-regulated, iron-regulated transporter-like protein) transporter plays an important role in regulating the uptake, transport, and accumulation of microelements in plants. Although some studies have identified ZIP genes in wheat, the significance of this family is not well understood, particularly its involvement under Fe and Zn stresses. In this study, we comprehensively characterized the wheat ZIP family at the genomic level and performed functional verification of three TaZIP genes by yeast complementary analysis and of TaZIP13-B by transgenic Arabidopsis. Totally, 58 TaZIP genes were identified based on the genome-wide search against the latest wheat reference (IWGSC_V1.1). They were then classified into three groups, based on phylogenetic analysis, and the members within the same group shared the similar exon-intron structures and conserved motif compositions. Expression pattern analysis revealed that most of TaZIP genes were highly expressed in the roots, and nine TaZIP genes displayed high expression at grain filling stage. When exposed to ZnSO4 and FeCl3 solutions, the TaZIP genes showed differential expression patterns. Additionally, Six ZIP genes responded to zinc-iron deficiency. A total of 57 miRNA-TaZIP interactions were constructed based on the target relationship, and three miRNAs were downregulated when exposed to the ZnSO4 and FeCl3 stresses. Yeast complementation analysis proved that TaZIP14-B, TaZIP13-B, and TaIRT2-A could transport Zn and Fe. Finally, over-expression of TaZIP13-B in Arabidopsis showed that the transgenic plants displayed better tolerance to Fe/Zn stresses and could enrich more metallic elements in their seeds than wild-type Arabidopsis. This study systematically analyzed the genomic organization, gene structure, expression profiles, regulatory network, and the biological function of the ZIP family in wheat, providing better understanding of the regulatory roles of TaZIPs and contributing to improve nutrient quality in wheat crops.